2009
DOI: 10.1177/1469787409343186
|View full text |Cite
|
Sign up to set email alerts
|

The power of in-class debates

Abstract: The students in three sections of a class rated their knowledge and identified their view before and after each of five in-class debates. The degree of self-reported knowledge was significantly different after four of the five debates. Between 31% and 58% of participants changed their views after participating in or observing each debate. Some changed their opinion even when they defended the side consistent with their original view. Despite their fears of participating in a debate, prior to the first debate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
76
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 18 publications
(19 reference statements)
4
76
1
4
Order By: Relevance
“…This limited use may relate to the criticisms levied against the Socratic debate method, for being too adversarial and combative. Yet, research has indicated the effectiveness of debates in supporting learning in a variety of disciplines including economics, education, history, marketing, medicine, nursing, psychology, sociology and social work (Dundes, 2001;Helenius et al, 2006;Kennedy, 2009;Omelicheva & Avdeyeva, 2008). There is, however, a significant dearth of literature specifically reflecting on the use of debates in teaching geography, despite the range of topics in the discipline which offer potential for such a method.…”
Section: Debates Within Teachingmentioning
confidence: 98%
See 4 more Smart Citations
“…This limited use may relate to the criticisms levied against the Socratic debate method, for being too adversarial and combative. Yet, research has indicated the effectiveness of debates in supporting learning in a variety of disciplines including economics, education, history, marketing, medicine, nursing, psychology, sociology and social work (Dundes, 2001;Helenius et al, 2006;Kennedy, 2009;Omelicheva & Avdeyeva, 2008). There is, however, a significant dearth of literature specifically reflecting on the use of debates in teaching geography, despite the range of topics in the discipline which offer potential for such a method.…”
Section: Debates Within Teachingmentioning
confidence: 98%
“…Debates as a method of teaching began in ancient Greece with the 'father of debate', Protagoras of Abdera (481-411 BC) (Smith, 1918;Kennedy, 2009). Whilst academics in the 1980s highlighted debate as "a promising teaching device" (Lewin & Wakefield, Jr., 1983, p.116) only certain disciplines, such as law, have taken the method on board to any great extent.…”
Section: Debates Within Teachingmentioning
confidence: 99%
See 3 more Smart Citations